Aplikasi Petani Millenial Meningkatkan Produktivitas Bidang Pertanian: Millennial Farmer App Improves Productivity in Agriculture - Putri, Roissa Nathania; Rozaki, Zuhud; Wulandari, Retno; Suryani, Cahyaningrum Arie (Universitas Muhammadiyah Yogyakarta, 2024)
The digital economy is currently growing around the world, including Indonesia, and is characterised by an increase in the number of Internet users. In early 2021, the number of Internet users in Indonesia reached 202.6 million, an increase of 15.5 per cent or 27 million compared to January 2020. Especially when the COVID-19 pandemic has affected service mechanisms and caused changes in consumer behaviour. Economic actors need to innovate new consumer habits from traditional buying and selling models to adapt to e-commerce. The benefits of digitalisation for Indonesia's economic development include increased market share, ease of transactions, increased production, easier payments, and more diverse promotions. On the other hand, the disadvantages include a lack of labour absorption and vulnerability to fraud and plagiarism. In addition, the financial sector, agricultural sector, cultural sector, tourism, and creative industry have the potential to grow further in the digital era. The Millennial Farmer application is an innovative solution that aims to increase productivity and efficiency in agriculture. By capitalising on the development of information technology and smartphone penetration among millennial farmers, the app is designed to provide easy and quick access to the latest information, best farming techniques, and other resources that can improve agricultural yields. The utilisation of e-commerce in the marketing of agricultural products has also brought about many changes. The development of the Millennial Farmer App is expected to help farmers overcome challenges in modern agriculture, such as climate change, market fluctuations, and the constant need for innovation. By bringing together traditional expertise and modern technology, this application becomes an effective tool in advancing the agricultural sector, encouraging economic growth in rural areas, and creating sustainability in food supply.